Respon Kemiskinan dan Pendapatan Terhadap Penyalur Bank Perkreditan Rakyat Berdasarkan Demografi Indonesia - Azka Rizkina; Nur Aidar; M. Rasyidin; Al Mahfud Saputra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the response of poverty and income to rural credit bank distributors based on Indonesian demographics. The data used is panel data, a combination of time series and cross-section data. The time series data used is data from 2014-2024 obtained from the Central Statistics Agency (BPS). The regions analyzed in this study are Indonesia, which covers 34 provinces. The total sample in this study is 374 samples. The analytical method in this study uses the Autoregressive Distributed Lag (ARDL) model and uses time series data. However, this study uses the ARDL model in the form of panel data. The use of the ARDL model is to see the role of time, theoretical justification and the relationship between one variable and another. The results of the study indicate that poverty and income have a long-term effect on consumer credit distribution. This is evidenced by the probability value of (0.000). Meanwhile, in the short term, only the income variable influences credit distribution. This can be seen based on the 10 percent probability value level, which is 0.08.